Patients admitted in an Intensive Care Unit with severe clinical manifestations of Influenza, october-december 2009 - Yenisey Quintero Mendez; Jorge Luis Ulloa Capestani; Rudis Monzón Rodríguez; Francisco García Valdés; Ramón E Álvarez Cepero; Jaime Geroy Gómez; Pablo Rodríguez Díaz; Alfredo Dario Espinosa Brito; Yanli Vázquez Villazón; Diley Moreno Ruiz; Octavio Rivero Rodríguez (Medisur)
A descriptive study of a series of cases was carried out, where 109 patients with the presumptive diagnosis of severe clinical pictures of Influenza were included, the total of them admitted in one of our Intensive Care Units (ICU), prepared for that purpose during the recent pandemic, during the period comprised between October 1 and December 31, 2009. There were 62 women (56,9%), of which 19 were pregnant or postpartum women (17,4%). The mean age of the sick persons of this serie was of 52,53 ± 22,54 years. The beginning of symptoms before the time of admission revealed an average of 4,90 ± 4,37 days. The predominant symptoms were: cough in 93 patients (85,3%), dyspnea in 86 (78,9%), fever in 76 (68,8%) and general symptoms of asthenia and anorexia in 76 (68,8%). In the physical exam, the most frequent signs were: polypnea in 86 (78,9%) and wet rales in 65 (59,6%). Personal antecedents were informed by patients suffering arterial hypertension in 31 (28,4%), bronchial asthma and chronic obstructive lung disease in 26 (23,9%), diabetes in 19 (17,4%), ischemic heart disease in 19 (17,4%), alcoholism in 5 (4,6%) and valvulopathies in 4 (3,7%). Among the signs found in the thorax´s radiographies at the moment of admission, it prevailed the pattern of radiopacity diffuse hilar and bilateral parahilar in 31 patients (28,4%), followed by bilateral diffuse opacities toward medial and inferiors lobes in 16 (14,7%), unilateral diffuse radiopacity in 12 (11,0%), increment in the broncovascular network in 13 (11,9%), lobar consolidation in 7 (6,4%) and pleural esfusion in 5 (4,6%). In 25 cases the initial X-ray films were normal. In electrocardiograms, alterations were verified of ST-T in 12 sick persons (11,0%), sinusal tachicardia in 12 (11,0%), supraventricular arrhythmias (that included acute auricular fibrillation and supraventricular paroxysmal tachicardia) in 7 (6,4%) and ventricular arrhythmias in 2 (1,8%). The complications verified with more frequency were the cardiovascular ones (left ventricular failure and diverse types of arrhythmias) in 15 sick persons (13,4%), the multiple failure of organs in 14 (12,8%), the bacterial infection in 6 (5,6%) and the adult respiratory distress syndrome in 2 (1,9%). 19 patients required mechanic ventilation (17,4%). We only confirmed the diagnosis by RCP-TR in 8 cases (7,3%). There were 17 deceased (although no pregnant or postpartum women), for a letality of 15,6%. These results were compared with the available literature and comments were made.